A Novel Fractional Slot Concentrated Winding Yokeless Counter-Rotating Dual-Rotor Permanent Magnet Machine - Zhitong Ran; Zi-Qiang Zhu; Hai Xu; Yanjian Zhou; Liang Chen; Lei Yang (IEEE Access)
Radial-flux fractional slot concentrated winding (FSCW) yokeless counter-rotating dual-rotor permanent magnet (YCDRPM) machines are proposed and investigated in this paper. Counter-rotating operation is required for special applications, such as washing machines, counter-rotating wind power generators, and underwater vehicles. The YCDRPM machine integrates magnetic gear and the FSCW PM machine. Its dual-rotor counter-rotating operation is achieved by utilising the magnetic field modulation theory in the FSCW PM machine, which is proved by the analytical method. The operation principle and three feasible slot/pole number combinations are investigated under different operation modes. The FSCW YDCRPM machine is analysed using an analytical method and validated by finite element analysis (FEA) and experiment. The FSCW YCDRPM machine not only operates as a counter-rotating DRPM machine but also can utilise the magnetic gearing effect to enhance the output torque. Experiments on a prototype FSCW YCDRPM machine validate the results. The proposed machine shows counter-rotating functionality and flexibility in rotational speed and torque. The machine used in the specific application will be researched in the future based on specific application requirements for practical implementation.